Pengaruh Kesadaran, Kualitas Pelayanan dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Restoran (Studi Kasus Pajak Restoran yang terdaftar pada Badan Pelayanan Pajak Daerah Kabupaten Sidoarjo) - Purnamasari, Maya Haningrum; Muslimin, Muslimin (Jambura Economic Education Journal, 2025)
The focus of the following research is how tax witnesses, services provided, and taxpayer awareness influence restaurant taxpayer compliance registered with the Sidoarjo Regency Regional Tax Service Agency. This study applies a quantitative approach. This study found that tax compliance is not affected by service quality; On the contrary, awareness of taxpayers and tax sanctions has an impact on tax compliance. The conclusions obtained from this research are (1) taxpayer awareness influences taxpayer compliance in restaurants in Sidoarjo district, the presence of actions in reporting in a timely manner with the correct amount can be said to be a form of taxpayer awareness, (2) Service quality has no effect on restaurant taxpayer compliance in Sidoarjo Regency, which means that the services of tax officers in agencies can still be considered weak or less than optimal, and (3) tax sanctions affect restaurant taxpayer compliance in Sidoarjo Regency, tax sanctions are administrative sanctions that force taxpayers to comply with tax regulations . Thus, tax sanctions can have an impact on taxpayer compliance.